PENGARUH PENERAPAN ROUTING I-BGP TERHADAP WAKTU FAILOVER DALAM JARINGAN LOKAL - Hartanto, Agus; Surono, Surono; Wicaksana, Dinar Anggit (Jurnal Transformatika, 2025)
The reliability of computer networks is a crucial element in supporting various sectors in the digital era. Failover, an automatic switching mechanism to a backup route when the main route fails, heavily depends on response speed and the capability of routing protocols. This study evaluates the effectiveness of Internal Border Gateway Protocol (I-BGP) in accelerating failover time on a local network based on Mikrotik connected via VPN. The performance of I-BGP is compared with OSPF, RIP, and Static Routing through tests on failover time, packet loss, and bandwidth efficiency. The results show that I-BGP has the fastest failover time (0.51 seconds), minimal packet loss (2 packets), and the highest bandwidth utilization (95%). ANOVA testing confirms significant differences among the protocols (F=776.898, p